Respuestas

2014-01-04T08:48:27+01:00
Problema 6)
(a^{b}+a^{-b})(a^{b}-a^{-b})(a^{4b}+1+4^{-4b})  \\ \\ = (a^{2b}-a^{2b})((a^{4b}+1+4^{-4b})   \\ \\ = (a^{2b}*a^{4b})+(a^{2b}*a^{-4b})+(a^{2b}*1)-(a^{-2b}*a^{4b})-(a^{-2b}*a^{-4b})[tex]   \\ \\  =  a^{6b}+a^{-2b}+a^{2b}- a^{2b}-a^{-6b}-a^{-2b}   \\ \\ =  a^{6b}- a^{6b}


Problema 9)
  \frac{( \sqrt[4]{x}+\sqrt[4]{y}){2}-(\sqrt[4]{x}-\sqrt[4]{y})^{2}}{ \sqrt[4]{xy}}  \\  \\  =  \frac{( \sqrt[4]{x}+ \sqrt[4]{y}+ \sqrt[4]{x}- \sqrt[4]{y})(\sqrt[4]{x}+ \sqrt[4]{y}-\sqrt[4]{x}+ \sqrt[4]{y})}{ \sqrt[4]{xy}}  \\  \\  =  \frac{ 2\sqrt[4]{x}*2 \sqrt[4]{y}}{ \sqrt[4]{xy}}   \\  \\ =  \frac{4 \sqrt[4]{xy}}{ \sqrt[4]{xy}}  \\  \\  L = 4


Problema 17)
Si   \sqrt{x+a+b} -  \sqrt{x-a-b}  = a+b  \\  \\ =  \sqrt{x+a+b-x+a+b} = a+b  \\  \\ =  \sqrt{2a+2b}=a+b  \\  \\ =    (\sqrt{2a+2b})^{2} =(a+b)^{2} \\  \\ = 2a + 2b = (a+b)^{2}  \\  \\ = 2(a+b)=(a+b)^{2}  \\  \\ =a+b = 2 \\  \\ =Por lo tanto: \\  \\ = N=2
En el problema 6) donde dice "tex" es -(a elevado a la -2b)